Study of Consumer Attitudes Toward Television Advertising Using Celebrity Endorser - Asmirandi Noor Hudha; Anas Hidayat (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2009)
This research analyzed how the attractiveness of a celebrity endorser is able to influ-ence customers’ brand choice behavior and how customers perceive celebrity-based television advertising. The study is based on an empirical research approach, which use a convenience sample of 150 students who lives in Yogyakarta. The respondents rate the attractiveness of ce-lebrity-based on television advertising and the influence of celebrity-based television advertis-ing on consumers’ brand choice behavior. The sample of advertisement in this research is XL television advertising which is featuring Raffi Ahmad, a famous celebrity. The data evaluated by using several statistical techniques, including Descriptive analysis, and Analysis of Variance (One Sample t-Test) Based on the research findings and the analysis, it is proved that the ce-lebrity-based television advertising has positively attracted the consumers. As a consequence, this response significantly influences the consumers’ brand choice behavior. It can be con-cluded that the attractiveness of celebrity-based on television advertising is likely to have a positive relationship to consumers and celebrity-based television advertising is likely to have a positive influence toward consumers’ brand choice behavior.Keywords: celebrity concept, power of celebrity endorsement, attitude towards the ad and brand, endorser selection criteria